2012
DOI: 10.1007/s12194-012-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric properties and clinical application of an a-Si EPID for dynamic IMRT quality assurance

Abstract: Dosimetric properties of an amorphous silicon electronic portal imaging device (EPID) for verification of intensity-modulated radiation therapy (IMRT) were investigated as a replacement for conventional verification tools. The portal dosimetry system of Varian's EPID (aS1000) has an integrated image mode for portal dosimetry (PD). The source-to-imager distance was 105 cm, and there were no extra buildup materials on the surface of the EPID in this study. Several dosimetric properties were examined. For clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…These devices were initially developed to improve the accuracy of patient setup (1) in the 1980s and have become important equipment for quality control (QC) and quality assurance (QA) in radiotherapy. By obtaining MV-level transmission images through a fluorescence imaging system, an EPID can be used for light field consistency verification, isocenter verification, treatment bed movement accuracy verification, multileaf collimator (MLC) QC, and pretreatment patient-specific QA (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…These devices were initially developed to improve the accuracy of patient setup (1) in the 1980s and have become important equipment for quality control (QC) and quality assurance (QA) in radiotherapy. By obtaining MV-level transmission images through a fluorescence imaging system, an EPID can be used for light field consistency verification, isocenter verification, treatment bed movement accuracy verification, multileaf collimator (MLC) QC, and pretreatment patient-specific QA (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…18,31,32 Unfortunately, EPIDs exhibit "ghosting" (persistent signal after irradiation cessation) and are extremely sensitive to lower energy photons and thus to the non-water equivalence (attenuation) of their own construction. [32][33][34] Fundamentally limiting the accuracy and utility of all the foregoing approaches is the dosimeter's lack of proximity to the target volume. In this sense, in vivo dosimetry is, in clinical vernacular, something of a misnomer in that one does not truly measure the deposited dose in situ.…”
mentioning
confidence: 99%
“…[15] Results showed that cine mode can record the rapid temporal changes in dose rate that occur during dynamic MLC deliveries with performance similar to integrated mode and ionization chamber. The slightly lower response of the EPID operated in cine to ionization chamber is not related to the cine mode itself as integrated mode has a similar lower response.…”
Section: Discussionmentioning
confidence: 99%